Water management in mountainous Jardhar Village, Chamba Block, Uttarakhand, India - Kamble, RK (International Journal of Environment, 2014)
An attempt has been carried out to assess water management practices adopted by Jardhar villagers in Chamba block of Uttrakhand. The rain water during rainy season got collected in chahals (mountainous tanks) on top of mountains. The rain water which got collected in these structures percolates through mountains and forms number of small streams which were perennial in nature. The water from these streams were received in a small metal tank at the end of stream in the mountain and through a steel pipe this collected water was diverted and collected into a cement tank at an elevated location at the entrance of the village. From this elevated water reservoir water was distributed at various locations in the village through public stand posts. The sustainable utilization of water in this mountainous area paved way for availability of water throughout the year and thus can sustain the population in such a topographic region. This traditional water management in Jardhar village has set an example of water management which can be adopted in such terrains throughout the world. DOI: http://dx.doi.org/10.3126/ije.v3i1.9946 International Journal of Environment Vol.3(1) 2014: 93-100